ANALISIS URGENSITAS PENDIDIKAN DALAM DUNIA BISNIS DALAM MENINGKATKAN MOTIVASI KEWIRAUSAHAAN: STUDI KASUS MAHASISWA UNIVERSITAS NUSA PUTRA - SIPAYUNG, ISKANDAR; MINTAWATI, HESRI; ALBERT, JHONI; PRADESA, KOHAR; VERIANTI, GIRI (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2024)
This study aims to examine the role of entrepreneurship education in enhancing entrepreneurial motivation among students. The limited availability of adequate employment opportunities in Indonesia remains a current issue. To provide a solution to this problem, the Indonesian government through the Ministry of Cooperatives and Small and Medium Enterprises (Kemenkop) has initiated the National Entrepreneurship Movement (Gerakan Kewirausahaan Nasional/GKN). This program, developed as a step to increase the number of entrepreneurs, is expected to become a solution to the limited job opportunities in Indonesia. In this regard, the role of entrepreneurship education must be maximized to enhance students' motivation to have the intention, determination, and capability to become entrepreneurs. Over time, the formation of entrepreneurial values has not only been present among entrepreneurs and businesses but has also extended into education, where activities increasingly require an entrepreneurial spirit. Entrepreneurship in education aims to create holistic individuals who possess the character, understanding, and skills necessary to become entrepreneurs. Essentially, entrepreneurship education is carried out by school principals, teachers, and educational staff (counselors), with educators being part of the education community. ABSTRAKPenelitian ini bertujuan untuk mengkaji peranan pendidikan kewirausahaan dalam meningkatkan motivasi berwirausaha dikalangan mahasiswa. keterbatasan lapangan pekerjaan yang memadai di indonesia masih menjadi permasalahan yang dihadapi saat ini. Guna memberi solusi untuk permasalahan tersebut Pemerintah Indonesia melalui Kementerian Koperasi dan UKM (Kemenkop) menggalakan Gerakan Kewirausahaan Nasional (GKN). Program yang dibuat sebagai langkah untuk terus memajukan jumlah wirausaha yang ada ini diharapkan dapat menjadi solusi permasalahan keterbatasan lapangan pekerjaan di Indonesia. Terkait hal tersebut, maka disinilah peranan pendidikan kewirausahaan harus dapat dimaksimalkan guna meningkatkan motivasi mahasiswa untuk memiliki niat, tekad dan kemampuan untuk menjadi wirausaha. Dalam perkembangannya, pembentukan nilai-nilai kewirausahaan tidak hanya dikalangan pengusaha dan dunia usaha saja tetapi sudah merambah dunia pendidikan, dimana kegiatannya juga sangat membutuhkan jiwa kewirausahaan. Kewirausahaan dalam pendidikan bertujuan untuk menjadikan manusia secara holistik, sebagai manusia yang memiliki karakter, pemahaman dan keterampilan sebagai wirausaha. Pada dasarnya kewirausahaan pendidik dilakukan oleh kepala sekolah, guru dan tenaga kependidikan (konselor), pendidik tentunya sebagai masyarakat pendidikan.